2012
DOI: 10.1016/j.adt.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Energies and E1, M1, E2, M2 transition rates for states of the 2s22p, 2s2p2, and 2p3 configurations in boron-like ions between N III and Zn XXVI

Abstract: Energies, E1, M1, E2, M2 transition rates, line strengths, oscillator strengths, and lifetimes from relativistic configuration interaction calculations are reported for the states of the (1s 2 )2s 2 2p, 2s2p 2 , and 2p 3 configurations in all boron-like ions between N III and Zn XXVI. Valence, core-valence, and core-core correlation effects were accounted for through singledouble multireference (SD-MR) expansions to increasing sets of active orbitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 29 publications
3
64
0
Order By: Relevance
“…It can be seen from the table that there is extremely good agreement between Model 2 and Rynkun et al (2012), with discrepancies of less than 5%. The Model 1 calculation also exhibits good agreement with Rynkun et al (2012), since the differences are less Rynkun et al (2012).…”
Section: Transition Probabilitiesmentioning
confidence: 70%
See 4 more Smart Citations
“…It can be seen from the table that there is extremely good agreement between Model 2 and Rynkun et al (2012), with discrepancies of less than 5%. The Model 1 calculation also exhibits good agreement with Rynkun et al (2012), since the differences are less Rynkun et al (2012).…”
Section: Transition Probabilitiesmentioning
confidence: 70%
“…Typically, any differences were less than 15% for the forbidden transitions and 5% for the dipole-allowed transitions. The present transition probabilities were also compared with the extensive calculation of Rynkun et al (2012), and very good agreement was found.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations